Removal of CO2 from CH4 and CO2 capture in the presence of H2O vapour in NOTT-401 - Lara García, Hugo A. (2015)
From a binary equimolar gas-mixture of CO2 and CH4, NOTT-401 exhibits CO2 separation from CH4. By kinetic uptake experiments, NOTT-401 shows a maximum of 1.47 wt% CO2 capture at 30 °C and a significant 7-fold increase (∼9.90 wt%) in CO2 capture under 40% relative humidity